ANALISIS PENERAPAN PROBLEM BASED LEARNING MELALUI PROYEK DIORAMA DALAM MENDORONG KETERLIBATAN PESERTA DIDIK - Mufihatun, Irma; Krisdiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of the Problem Based Learning (PBL) model through a diorama project in encouraging student engagement in a Natural and Social Sciences (IPAS) lesson. The research was motivated by the demand of the Kurikulum Merdeka for student-centred learning that actively involves learners, whereas classroom practice still tends to be teacher-dominated. This study aims to describe the implementation of PBL through the diorama project and to analyse the forms of behavioural, emotional, and cognitive engagement that emerge among students. A qualitative descriptive approach with a case-study design was used, and data were collected through direct observation of guided teaching practice in a fourth-grade class of 20 students at SD Negeri Trangsan 01. The results show that PBL, combined with the "Environmental Hero" diorama project, encouraged student engagement through orientation and apperception activities, problem identification from video stimuli, group investigation in constructing the diorama, presentation of group work, and closing reflection. Students demonstrated active participation, positive enthusiasm, cooperation, and critical thinking, although time management during the presentation and educational-game sessions still needs improvement. This study concludes that the PBL model through project-based, hands-on media such as dioramas is effective in fostering multidimensional student engagement in elementary science learning